Enabling Technologies for Handwashing with Soap : A Case Study on the Tippy-Tap in Uganda - Biran, Adam (World Bank, Washington, DC, 2014)
The Water and Sanitation Program's (WSP) Global scaling up handwashing project is testing whether innovative promotional approaches to behavior change can generate widespread and sustained improvements in household hygiene and sanitation practices in Peru, Senegal, Tanzania, and Vietnam. The purpose of this study was to document the process through which tippy-taps were promoted to qualitatively explore the results and to draw out lessons for future interventions. Handwashing with soap at key times is believed to be an effective and highly cost effective means of reducing diarrhea incidence. However, global rates of handwashing with soap are frequently low, particularly among the poor, who also face the greatest threat from infectious diseases. Access to a convenient handwashing station has been found to be associated with higher rates of handwashing and decreased fingertip contamination. Tippy-taps were an acceptable means of providing a low cost enabling technology for handwashing in this population. Anecdotally they have increased rates of handwashing after latrine use. However, uptake appeared driven by the 'push' of the intervention rather than the 'pull' of the technology and the extent to which spontaneous uptake and sustained use can be achieved in the absence of intensive intervention activities is not known. Respondents in non model villages had little contact with model villages and were largely unaware of the tippy-tap. The interventions were labor intensive and probably difficult to scale-up.